Sistemas dinâmicos discretos: - Silva, Nelly Almeida da (Universidade Federal do Tocantins, 2023)
This work presents an introduction to Discrete Dynamic Systems, an area that has great prominence in modeling phenomena and predicting future events based on past events. In the study of these systems, the difference equations have great prominence, being these a discrete version of the differential equations. Thus, we will present some concepts that help in solving these equations, such as the concepts of homogeneous and non-homogeneous